ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø·Ù„Ø¨Ø© ÙÙŠ Ø§Ù„Ø¥Ù†Ø´Ø§Ø¡ Ø¨Ø§Ù„ØµÙˆØ± Ø§Ù„Ù…ØªØ³Ù„Ø³Ù„Ø©: Ø¯Ø±Ø§Ø³Ø© ØªØ¬Ø±ÙŠØ¨ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ù…Ù†Ø§Ø± Ø§Ù„Ø¹ØµØ±ÙŠ - Azizah Azizah (Jurnal Ilmiah Didaktika, 2015)
Arabic writing is an important subject that must be studied by fifth grade students at Al-Manar boarding school. However, many students were bored and less motivated to participate in the teaching learning process of the lesson. The main cause of this problem is due to the use of traditional methods in teaching. Teachers do not use media when deliver the lesson, besides there is no particular handbook. Moreover, the lack of studentsâ€™ motivation is another problem faced by the teacher in teaching learning process. Some students feel bored with traditional methods used, and even some of them do not understand the meaning of words because their shortcoming in memorization and Arabic grammar skill (qawÄâ€™id). Based on the this problem, this experimental research implements picture series to develop the studentsâ€™ abilities and motivations in the learning process of composing lesson. The results of this study show that the use of picture series in teaching insyÄâ€™ has positive impact in developing competency and motivation of fifth grade students at Al-Manar boarding school. Mengarang merupakan materi pembelajaran yang penting dipelahari oleh siswa kelas lima di Pesantren Modern Al-Manar, dan proses belajar mengajar pada materi ini membosankan dan tidak termotivasi. Penyebab utama dalam masalah ini adalah guru menggunakan metode tradisional dalam mengajar, tidak menggunakan media pembelajaran bervariasi, dan tidak ada buku pegangan. Adapun masalah yang dihadapi guru adalah lemahnya minat murid dan perhatiannya dalam pembelajaran mengarang dalam bahasa Arab (insyÄâ€™), karena murid merasa bosan dengan metode tradisional yang digunakan guru saat mengajar. Sebagian siswa justru tidak memahami arti kata atau pola dasarnya. Hal ini disebabkan minimnya penguasaan kosa kata siswa dan lemahnya penguasaan ilmu tata bahasa (QawÄâ€™id). Dalam penelitian berikut peneliti mengajar insyÄâ€™ dengan menggunakan gambar berseri. Hasil penelitian ini menunjukkan bahwa pembelajaran dengan menggunakan gambar berseri efektif meningkatkan kemampuan siswa dalam mengarang bahasa Arab dan mempunyai pengaruh yang positif untuk meningkatkan motivasi siswa kelas lima di Pesantren Modern Al-Manar.